Technical challenges in the application of adaptive management - Williams, Byron K.; Brown, Eleanor D. (Biological Conservation, 2016)
Adaptive management is an approach for simultaneously managing and learning about natural resources, by acknowledging uncertainty and seeking to reduce it through the process of management itself. Adaptive decision making can be applied to pressing issues in conservation biology such as species reintroduction, disease and invasive species control, and habitat restoration, as well as to management of natural resources in general. After briefly outlining a framework and process for adaptive management, we focus on an overview of the key technical issues related to problem framing and the ability of resource managers to learn from their experience. These technical issues include the treatment of uncertainty and its propagation over time; nonstationarity in long-term environmental trends; the applicability of adaptive management across scales; requirements for models and management alternatives that promote learning; the value of the information produced with adaptive management; the challenge to management of uncertainty and surprise; and institutional (social) learning. To accommodate these and other challenges that are now coming into focus, the learning-based approach of adaptive management will need to be adjusted and expanded in the future.
Keywords: Adaptive Management; Learning; Nonstationarity; Resilience; Uncertainty; Value of information

Global Learning for Adaptive Management (GLAM) - DFID (DFID Development Tracker, 2016)
To improve the value for money and impact of development interventions by promoting the use of better monitoring, evaluation and learning strategies that support development programmes to gather and respond to emergent evidence on the effects of interventions, as well as changes in the development context. The Global Learning for Adpative Management programme will make available technical assistance to DFID, USAID and partners to develop this ‘adaptive management’ approach, as well as build an evidence base to understand links between the use of adaptive management and more effective, efficient, relevant and sustainable development interventions.

Putting learning at the centre: Adaptive development programming in practice - Valters, Craig; Cummings, Clare; Nixon, Hamish (ODI, 2016)
Adaptive programming suggests, at a minimum, that development actors react and respond to changes in the political and socio-economic operating environment. It emphasises learning and the development practitioner is encouraged to adjust their actions to find workable solutions to problems that they may face. Being prepared to react to change may seem like common sense – and indeed it is. However much development thinking and practice remains stuck in a linear planning model which discourages learning and adaptation, in part because projects are seen as ‘closed, controllable and unchanging systems’ (Mosse, 1998: 5). This paper critically engages with this problem and makes clear why and how learning needs to be at the centre of adaptive development programming. It begins by clarifying why and what kind of learning matters for adaptive programming. The paper then turns its focus to how strategies and approaches applied throughout a programme’s conception, design, management and M&E can enable it to continually learn and adapt.
Keywords: IMPORTANT

Adaptive Management Leaders Launch Practical Adaptation Network (PAN) - Labs, Feedback (FeedbackLabs, 2016)
Great things can happen at the frontier of theory and practice. When Feedback Labs worked with USAID’s Global Development Lab to bring together leaders in adaptive management at the White House on June 15th, we were pleased that we were able to move past the ongoing conceptual conversations toward discussing what we could do in concrete terms to implement adaptive management in practice.

SAVI Approach Paper 11: Managing and Staffing an Adaptive Citizen Engagement Programme - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme putting learning and adaptation at the centre of all decision-making. In relation to management and staffing SAVI has established the following approaches to facilitate this: – An adaptive approach to programme management: Full time strategic technical leadership, that works closely with and complements...

Adaptive Management in Practice: a case study on the Prospects program - Maclay, Chris (Mercy Corps, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT

Adaptive Management looks like it’s here to stay. Here’s why that matters. - Green, Duncan (From Poverty to Power, 2016)
First installment of reflections on my US trip. This is on the rise of adaptive management approaches in USAID, and some of the questions it raises
Keywords: IMPORTANT

Learning to Adapt: Building Adaptive Management as a Core Competency in Development Practice - Ramalingam, Ben (Institute of Development Studies, 2016)
Key messages 1. Development policies and programs increasingly operate in situations of high complexity and uncertainty. 2. There are growing efforts across the sector to design, plan and implement more adaptive responses that are more relevant and appropriate in such contexts 3. At the heart of effective adaptive programming is the capability to gather, interpret and use knowledge, information and data in real-time 4. Strengthening this capability requires a positive enabling environment—including tools and methods, structures and processes, leadership and management and culture and mindsets. 5. For adaptive development to succeed, there needs to be greater attention and investment in both knowledge, information and data systems and in appropriate enabling environments
Keywords: IMPORTANT

ADAPT: Analysis Driven Agile Programming Techniques - IRC (International Rescue Committee (IRC), 2016)
A growing body of research indicates that aid agencies are most successful when able to operate flexibly, particularly in fragile environments. Yet our systems and tools are often too rigid to effectively address complex problems, and program incentives frequently undermine adaptation instead of supporting it. To drive improvements in impact we need to be better able to analyse the dynamics of a given situation, anticipate how these might evolve, and be sufficiently agile to adapt to changes in context and need.

Adaptive development: great progress and some niggles - Vowles, Pete (Medium, 2016)
After 3 years in DFID headquarters, championing adaptive approaches to the delivery of aid and development programmes, I am back in an…

Adaptive Programming: The “Space of Possibility” - Seavey, Sara Mizuta (USAID Learning Lab, 2016)
Sara Mizuta Seavey, M.A., is a Senior Program Officer at FHI360 for the Mobile Solutions Technical Assistance and Research (mSTAR) project, where she works with USAID’s Digital Development Team to conceive, design, and test how real-time data systems can enable a more adaptive and participatory approach to development. She is passionate about systems thinking and participatory approaches to international development. What does space travel have to do with international development?

Engaging Farmers in Climate Change Adaptation Planning: Assessing Intercropping as a Means to Support Farm Adaptive Capacity - Himanen, Sari J.; Mäkinen, Hanna; Rimhanen, Karoliina; Savikko, Riitta (Agriculture, 2016)
Agriculture is one of the most vulnerable and adaptation-prone sources of livelihood facing climate change. Joint adaptation planning by farmers and researchers can help develop practically feasible and environmentally and economically sound adaptation actions as well as encourage the proactive building of farm adaptive capacity. Here, the perceptions of Finnish farmers and rural stakeholders regarding intercropping, the cultivation of two or more crop genotypes together in time and space, as a means to prepare for climate change, were collected in an open workshop. Our aim was to identify the potentials and challenges associated with intercropping, its role as an adaptation strategy, and in farm adaptive capacity. Qualitative analysis revealed better yield security, increased nutrient and protein self-sufficiency, soil conservation and maintenance, reduced pathogen pressure and regulation of water dynamics as the main perceived potentials of intercropping. Potentials relating to the farm economy and environment were also recognized. The main challenges associated with intercropping were related to the lack of information on crop variety performance and optimal yielding in mixtures, industry and policy requirements for seed purity, more complicated crop management and harvesting, and the economic risks associated with experimenting with novel mixtures. Nitrogen-fixing legumes; deep-rooted species, such as lucerne (Medicago sativa L.); special crops, such as herbs in forage mixtures; and autumn-sown winter oilseeds and cereals were highlighted as the most promising intercrops. Because the recognized potentials relate to the safeguarding of field cropping from anticipated climate change and the associated weather variability, we conclude that intercropping can serve as one adaptation strategy to strengthen the adaptive capacity of Finnish farms. However, assuring markets and policies that allow the development of intercropping, performing experiments to assess the benefits and implement options in practice, and providing farmers and farm advisors with more knowledge on the method represent the critical prerequisites for the broader adoption of intercropping.
Keywords: Adaptation planning; Adaptive capacity; Climate change; ecological intensification; intercropping; yield security

Wildlife laws monitoring as an adaptive management tool in protected area management in Ghana: a case of Kakum Conservation Area - Wiafe, Edward Debrah (SpringerPlus, 2016)
INTRODUCTION: The wildlife laws of Ghana alienated the rural communities from forests and material well-being depended upon for their livelihood and this manifests itself in the progressive conflict between the park patrol staff and poachers from the fringes of the protected areas. CASE DESCRIPTION: The main aim of this study was to determine the impact of quantification of patrol efforts on indicators of illegal hunting activities that occur in rainforest protected areas, as a result of monitoring patrol operations and modifying the original plan. The specific objectives were to determine the optimal patrol efforts necessary to reduce illegal wildlife use to minimal; and the influence of the rainfall and seasonal activities on illegal wildlife use. DISCUSSION AND EVALUATION: The results indicated that as the patrol efforts increased the encounter with illegal wildlife use also increased until a certain point that the encounter rates started decreasing. Neither rainfall nor seasonal activities influenced the illegal activities and the patrol efforts. The protection staff of rainforest protected areas would work effectively to bring down illegal wildlife off-take to the barest minimum if monitored, quantified and provide feed-back. CONCLUSIONS: Illegal wildlife off-take can also be reduced by the protection staff if the original plans are made flexible to be adjusted. Recommendations for further studies have been made.

What is adaptive management? - Wilson, Gregory (ΔNTYLLES, 2016)
Recently there has been growing recognition that most development challenges are in actual fact ‘wicked’ problem that requires development actors to recognize that the optimal management approaches…

SAVI Approach Paper 12: Managing Programme Finances to Support Adaptive, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governance in ways that are effective in influencing reform, and that are able to take on a life of their own without continuing donor support. SAVI is also an adaptive programme, putting learning and adaptation at the centre of all decision-making. Money is used and...

Built to improve: Leveraging realtime M&E for adaptive youth employment programming - Skelton, John (Mercy Corps, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2016.08) - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

All about behaviour: KAPE, Adaptation and ' Sticky' Institutional Change - Power, Greg (Global Partners Governance, 2016)
This paper describes Global Partners Governance’s (GPG’s) approach to institutional reform and political change. Developed over the last decade of working in some of the most complex and sensitive political environments with politicians and officials in parliaments, political parties, ministries and local government, it describes the KAPE® (knowledge-application-practice-effect) methodology that we adopt to get ‘sticky’ institutional and behavioural change. Contents 1) Two dimensions of ‘adaptive programmes’: Flexible delivery and getting behaviour change 2) Enabling Change: KAPE and The Logic of Institutional Reform (Knowledge-Application-Practice-Effect) - K: Knowledge – Defining the problem and what to do about it - A: Application – Making Systems Work in Practice - P: Practice – Pockets of good practice and establishing ‘the new normal’ - E: Effect – Improved performance and the ‘Ripple Effect’ 3) Measuring Impact: Monitoring and Evolving 4) Conclusion: Behavioural insights, adaptive management and sticky change

Micropolitics in collective learning spaces for adaptive decision making - Tschakert, Petra; Das, Partha Jyoti; Shrestha Pradhan, Neera; Machado, Mario; Lamadrid, Armando; Buragohain, Mandira; Hazarika, Masfique Alam (Global Environmental Change, 2016)
Recent advances on power, politics, and pathways in climate change adaptation aim to re-frame decision-making processes from development-as-usual to openings for transformational adaptation. This paper offers empirical insights regarding decision-making politics in the context of collective learning through participatory scenario building and flexible flood management and planning in the Eastern Brahmaputra Basin of Assam, India. By foregrounding intergroup and intragroup power dynamics in such collective learning spaces and how they intersect with existing micropolitics of adaptation on the ground, we examine opportunities for and limitations to challenging entrenched authority and subjectivities. Our results suggest that emancipatory agency can indeed emerge but is likely to be fluid and multifaceted. Community actors who are best positioned to resist higher-level domination may well be imbricated in oppression at home. While participatory co-learning as embraced here might open some spaces for transformation, others close down or remain shut.
Keywords: Co-learning; Flood management; Participatory scenarios; Politics of adaptation; Power

Learning and adaptation: 6 pitfalls to avoid - Valters, Craig (Devex, 2016)

Adaptive Management Self-assessment tool - mercy Corps (Mercy Corps, 2016)
The Adaptive Management self-assessment tool has been designed to help teams assess the extent to which they have a supportive environment for adaptive management within their country program. The self-assessment tool helps you think about five different areas that have been identified as important for supporting adaptive management: 1. Culture & leadership 2. Dynamic teams 3. Appropriate analysis 4. Responsive implementation & operations 5. Enabling environment (for example donor funding and relationships)

Towards characterizing the adaptive capacity of farmer-managed irrigation systems: learnings from Nepal - Thapa, Bhuwan; Scott, Christopher; Wester, Philippus; Varady, Robert (Environmental change assessments, 2016)
Small-scale irrigation systems managed by farmers are facing multiple challenges including competing water demand, climatic variability and change, and socioeconomic transformation. Though the relevant institutions for irrigation management have developed coping and adaptation mechanisms, the intensity and frequency of the changes have weakened their institutional adaptive capacity. Using case examples mostly from Nepal, this paper studies the interconnections between seven key dimensions of adaptive capacity: the five capitals (human, financial, natural, social, and physical), governance, and learning. Long-term adaptation requires harnessing the synergies and tradeoffs between generic adaptive capacity that fosters broader development goals and specific adaptive capacity that strengthens climate-risk management. Measuring and addressing the interrelations among the seven adaptive-capacity dimensions aids in strengthening the long term sustainability of farmer-managed irrigation systems.

Delivering institutional reform at scale: Problem-driven approaches supported by adaptive programming - Manuel, Clare (DFID-LASER Programme, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). Second synthesis paper - Delivering institutional reform at scale: problem-driven approaches supported by adaptive programming February 2016 Drawing on our experience on the ground, this peer-reviewed paper suggests how problem driven approaches, supported by adaptive programme management can be implemented at scale in relation to donor programming aimed at institutional reform and improving state capability.
Keywords: IMPORTANT

Adaptive management: an overview of the concept and its practical application in the Scottish context - Blackstock, Kirsty; Brown, Katrina; Gimona, Alessandro; Prager, Katrin; Irvine, Justin (The James Hutton Institute, 2016)

The road to adaptive management: knowledge, leadership, culture and rules - Byrne, Karri Goeldner; Sparkman, Timothy; Fowler, Ben (The BEAM Exchange, 2016)
Keywords: IMPORTANT; Practice

Adaptive management: What it means for CSOs - O’Donnell, Michael (Bond, 2016)
Keywords: IMPORTANT

SAVI Approach Paper 14: Learning, Adaptation and Communications - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme, aiming to put learning and adaptation at the centre of all decision-making. Learning and adaptation takes place in SAVI at three levels: the work of partners; the work of SAVI delivery teams; and the enabling environment of the programme as a whole. Achieving...

Contracts for adaptive programming - Bryan, Kevin; Carter, Paddy (ODI, 2016)
Adaptive programming is an approach to development that encourages experimentation, learning & adaptation. This report examines the contractual underpinnings of this approach.

Monitoring, Evaluation and Learning approaches in an adaptive management context - Tsui, Josephine (EPS PEAKS, ODI, 2016)

edX MOOC: Adaptive Leadership in Development - edX (edX, 2016)
Gain the skills to be an adaptive leader in development and learn how to uncover local solutions to complex problems in developing countries.

Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Expertgruppen för biståndsanalys (EBA), 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

Using adaptive development to support feminist action - O’Neil, Tam (ODI, 2016)
This paper looks at how adaptive development is being applied by gender programmes and argues that gender and adaptive development communities have much to offer each other.

Real-Time Data for Adaptive Management at USAID - Doshi, Samir (2016)

‘Learning journeys’ for adaptive management – Where does it take us? - Ørnemark, Charlotte (Global Partnership for Social Accountability, 2016)
Keywords: IMPORTANT

Leading Change Through Adaptive Design - Berstein, Maya; Linsky, Marty (Stanford Social Innovation Review, 2016)
By integrating two practices—design thinking and adaptive leadership—social innovators can manage projects in a way that’s both creatively confident and relentlessly realistic.

From analysis to action: operationalising learning and adaptation in Savings at the Frontier - Salehi, Yusef (2016)
Keywords: IMPORTANT

Collaborating, Learning, and Adapting Framework & Key Concepts - USAID (USAID, 2016)
Although collaborating, learning, and adapting (CLA) are not new to USAID, they often do not happen regularly or systematically and are not intentionally resourced. The CLA framework above identifies components and subcomponents to help you think more deliberately about what approach to CLA might be best tailored to your organizational or project context. The framework recognizes the diversity of what CLA can look like in various organizations and projects while also giving CLA structure, clarity, and coherence across two key dimensions: CLA in the Program Cycle: how CLA is incorporated throughout Program Cycle processes, including strategy, project, and activity design and implementation; and Enabling Conditions: how an organization’s culture, business processes, and resource allocation support CLA integration. Organizations need both integrated CLA practices appropriate for their context and conducive enabling conditions to become stronger learning organizations capable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the principle that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development and improve aid effectiveness.

Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming - Alan (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Politics matters. Context too. And blueprints have limited value. Our strategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...

LEARN Monitoring, Evaluation, Research, and Learning Plan - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Adapting Aid: Lessons from six case studies - Algoso, Dave; Beloe, Jon; Hemberger, Alison; Hill, Philippa; Proud, Emma (MercyCorps & IRC, 2016)
Keywords: IMPORTANT

Collaborating, Learning and Adapting (CLA) - Maturity Matrix Overview - USAID (Policy, Planning and Learning, 2016)
Collaborating, Learning and Adapting (CLA) involves strategic collaboration, continuous learning, and adaptive management. CLA approaches to development include collaborating intentionally with stakeholders to share knowledge and reduce duplication of effort, learning systematically by drawing on evidence from a variety of sources and taking time to reflect on implementation, and applying learning by adapting intentionally. The purpose of the maturity matrix tool is to help USAID Missions think more deliberately about how to plan for and implement CLA approaches that fit the Mission’s context and needs. Through a set of easy-to-use cards, the CLA maturity matrix offers examples of what CLA looks like at different stages of maturity. USAID staff can use the decks of cards to both assess current practice and plan for the future. The maturity matrix consists of two decks of cards corresponding to the dimensions of CLA: ● CLA in the Program Cycle: By using the matrix cards to guide a conversation, teams can explore how well CLA is incorporated into the planning and implementation processes of the Program Cycle. ● Enabling Conditions: The cards encourage discussion of the conditions that can significantly influence how CLA and the Program Cycle are implemented at a Mission, including operating processes, organizational culture, and resourcing. Within these decks, the matrix covers 16 subcomponents of CLA. Each has one key concept card and five matrix cards that describe the component in practice, along a spectrum ranging from Not Yet Present to Institutionalized.

SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Programme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Nigeria Public Sector Accountability and Governance Programme - Business Case - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Exploring ways to reconcile accountability and learning in the evaluation of niche experiments - Regeer, Barbara J.; de Wildt-Liesveld, Renée; van Mierlo, Barbara; Bunders, Joske F. G. (Evaluation, 2016)
While evaluation is seen as a mechanism for both accountability and learning, it is not self-evident that the evaluation of niche experiments focuses on both accountability and learning at the same time. Tensions exist between the accountability-oriented needs of funders and the learning needs of managers of niche experiments. This article explores the differences in needs and expectations of funders and managers in terms of upwards, downwards and internal accountability. The article shows that as the multi-stakeholder contexts in which niche experiments take place give rise to various requirements, tensions in evaluation are essentially a specific manifestation of tensions between niche experiments and their multiple contexts. Based on our findings, an adjusted accountability framework is proposed, including several strategies that can reconcile a learning approach with accountability needs in niche experiments aiming to change current practices in a more sustainable direction.

What is impact? - Hearn, Simon; Anne, Buffardi (2016)
• Impact is a multi-dimensional concept. Some definitions focus on very precise understandings of impact, while others cast a much broader net. • How impact is defined and used has a significant effect on the design, management and evaluation of development programmes. • Development programmes should hold explicit conversations with different stakeholders about how impact is used and understood, in order to come to a shared understanding. • There are six dimensions of impact that may help development programmes be clearer about what they mean.

Doing things differently: Rethinking monitoring and evaluation to understand change - Saferworld (Saferworld, 2016)
Doing things differently: Rethinking monitoring and evaluation to understand change Learning paper Over the past four years, Saferworld has put in place a way of monitoring, evaluating and learning from our work focused on behaviour and relationship change. This paper outlines the process we have gone through to adapt, embed, and embrace an approach inspired by Outcome Mapping and Outcome Harvesting (OH). Key benefits of our monitoring, evaluation and learning approach are: It is simple, but promotes complex discussion and analysis. It allows conflict- and gender-sensitivity to be built into programmes; it promotes analysis of and adaptation to context. Bringing front-line staff and partners into wider conversations with others substantially increases cross-organisational learning.

Announcement of CLA Learning Network Launch - Lab, Learning (USAID Learning Lab, 2016)
USAID’s Bureau for Policy, Planning and Learning (PPL), together with the Bureau for Economic Growth, Education, and Environment’s localworks program, is pleased to announce the launch of a Learning Network focused on building the evidence base for Collaborating, Learning and Adapting (CLA).

Moving Targets, Widening Nets: monitoring incremental and adaptive change in an Empowerment and Accountability programme. The experience of the State Accountability and Voice Initiative in Nigeria - Derbyshire, Helen; Barr, Julian; Fraser, Steve; Mwamba, Wilf (DFID, 2016)
Keywords: IMPORTANT; Practice

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (DFID-LASER Programme, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

Impact evaluation for portfolio programmes on policy influence: Reflections on the Indonesian Poverty Reduction Support Facility - Mackenzie, Jessica; Hearn, Simon (Methods Lab, 2016)
• Donors are increasingly using portfolio-based programmes that embrace ‘good failure’ and adaptive, political programming. • However, measuring the impact of these programmes is challenging, especially for those working on policy influence and building country systems; not only do you need to measure the positive and negative impact of the overall portfolio, but also the different pathways tested. • Programmes, therefore, need a light-touch monitoring and evaluation system that allows it to remain flexible. • Good practice examples of portfolio-based programmes present six strategies to evaluate impact: 1. Develop appropriate logic models 2. Collect observational data throughout implementation 3. Develop stories of change or case studies 4. Understand causal relationships without a counterfactual 5. Purposefully select which activities to study 6. Be explicit about how impact will be valued across the portfolio. • These strategies are only useful if monitoring and evaluation is placed at the centre of programme decision-making.

Where have we got to on adaptive learning, thinking and working politically, doing development differently etc? Getting beyond the People’s Front of Judea - Algoso, Dave; Hudson, Alan (From Poverty to Power, 2016)
Dave Algoso and Alan Hudson at Global Integrity compare and contrast 9 different initiatives that are all heading in roughly the right direction in aid reform
Keywords: IMPORTANT

Assumptions, conjectures, and other miracles: The application of evaluative thinking to theory of change models in community development - Archibald, Thomas; Sharrock, Guy; Buckley, Jane; Cook, Natalie (Evaluation and Program Planning, 2016)
Unexamined and unjustified assumptions are the Achilles’ heel of development programs. In this paper, we describe an evaluation capacity building (ECB) approach designed to help community development practitioners work more effectively with assumptions through the intentional infusion of evaluative thinking (ET) into the program planning, monitoring, and evaluation process. We focus specifically on one component of our ET promotion approach involving the creation and analysis of theory of change (ToC) models. We describe our recent efforts to pilot this ET ECB approach with Catholic Relief Services (CRS) in Ethiopia and Zambia. The use of ToC models, plus the addition of ET, is a way to encourage individual and organizational learning and adaptive management that supports more reflective and responsive programming.
Keywords: Assumptions; Community development; Critical thinking; Evaluation capacity building; Evaluative thinking; International Development; Theory of change

Politically smart approaches to donor investment climate programming. A Guidance Note - LASER (DFID-LASER Programme, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Politically smart approaches to donor investment climate programming (and annexes) Revised February 2016 - sets out practical advice on how to adopt a politically smart (which requires being both ‘politically informed’ and ‘politically astute’) approach to programming. The annexes include a traffic light matrix for initial high level analysis; a problem diary template with examples; and an example of a flexible theory of change for adaptive, large scale programming
Keywords: Practice

Overcoming Premature Evaluation - Roche, Chris (2016)
Guest post from Chris Roche on practical ways of introducing adaptive management, learning from failure etc in aid programmes

How to design a monitoring and evaluation framework for a policy research project - Pasanen, Tiina; Shaxson, Louise (Methods Lab, 2016)
Policy research projects face a number of challenges: policy processes are complex, involve multiple actors and often feature a significant time-lag between research and what may or may not happen as a result of it. To complicate matters further, the scope and scale of policy research projects are increasingly moving away from single research studies towards multi-component, multi-site and multi-sector endeavours. These factors mean that developing an overarching monitoring and evaluation framework can be challenging. But it is not impossible. The guidance note aims to support the first steps in designing and structuring the M&E framework (that is, what aspects or areas of policy research projects to monitor and evaluate, why, when and how). It builds on an M&E framework for policy research projects developed and tested by the Research and Policy in Development (RAPID) programme of the Overseas Development Institute, and draws on case studies of how it has been used by RAPID and other research teams.

Assumption-aware tools and agency; an interrogation of the primary artifacts of the program evaluation and design profession in working with complex evaluands and complex contexts - Morrow, Nathan; Nkwake, Apollo M. (Evaluation and Program Planning, 2016)
Like artisans in a professional guild, we evaluators create tools to suit our ever evolving practice. The tools we use as evaluators are the primary artifacts of our profession, reflect our practice and embody an amalgamation of paradigms and assumptions. With the increasing shifts in evaluation purposes from judging program worth to understanding how programs work, the evaluator’s role is changing to that of facilitating stakeholders in a learning process. This involves clarifying purposes and choices, as well as unearthing critical assumptions. In such a role, evaluators become major tool-users and begin to innovate with small refinements or produce completely new tools to fit a specific challenge or context. We interrogate the form and function of 12 tools used by evaluators when working with complex evaluands and complex contexts. The form is described in terms of traditional qualitative techniques and particular characteristics of the elements, use and presentation of each tool. Then the function of each tool is analyzed with respect to articulating assumptions and affecting the agency of evaluators and stakeholders in complex contexts.
Keywords: Agency; Assumption-aware; Complex context; Complex programs; Participatory approaches; Program design; Program evaluation; Program tools; Theory-based

Balancing Inclusiveness, Rigour and Feasibility: Insights from Participatory Impact Evaluations in Ghana and Vietnam - van Hemelrijck, Adinda; Guijt, Irene (CDI, 2016)
This paper by Adinda Van Hemelrijck and Irene Guijt explores how impact evaluation can live up to standards broader than statistical rigour in ways that address challenges of complexity and enable stakeholders to engage meaningfully. A Participatory Impact Assessment and Learning Approach (PIALA) was piloted to assess and debate the impacts on rural poverty of two government programmes in Vietnam and Ghana funded by the International Fund for Agricultural Development (IFAD). We discuss the trade-offs between rigour, inclusiveness and feasibility encountered in these two pilots. Trade-offs occur in every impact evaluation aiming for more than reductionist rigour, but the pilots suggest that they can be reduced by building sufficient research and learning capacity.

PDIA Notes 2: Learning to Learn - Samji, Salimah (Building State Capability, 2016)
written by Peter Harrington After over two years of working with the government of Albania, and as we embark on a new project to work with the government of Sri Lanka, we at the Building State Capa…

Summarising portfolio change: results frameworks at organisational level - Simister, Nigel (Intrac, 2016)

Innovation for International Development: Navigating the Paths and Pitfalls - Ramalingam, Ben; Bound, Kirsten (NESTA, 2016)
Experiences, insights and practical advice from over 20 leading practitioners in innovation for international development, brought together in one collection.

Future oriented conservation: knowledge governance, uncertainty and learning - Wyborn, Carina; van Kerkhoff, Lorrae; Dunlop, Michael; Dudley, Nigel; Guevara, Oscar (Biodiversity and Conservation, 2016)
Despite signiﬁcant progress in understanding climate risks, adaptation efforts in biodiversity conservation remain limited. Adaptation requires addressing immediate conservation threats while also attending to long term, highly uncertain and potentially transformative future changes. To date, conservation research has focused more on projecting climate impacts and identifying possible strategies, rather than understanding how governance enables or constrains adaptation actions. We outline an approach to futureoriented conservation that combines the capacities to anticipate future ecological change; to understand the implications of that change for social, political and ecological values; and the ability to engage with the governance (and politics) of adaptation. Our approach builds on the adaptive management and governance literature, however we explicitly address the (often contested) rules, knowledge and values that enable or constrain adaptation. We call for a broader focus that extends beyond technical approaches to acknowledge the sociopolitical challenges inherent to adaptation. More importantly, we suggest that conservation policy makers and practitioners can use this approach to facilitate learning and adaptation in the context of complexity, transformational change and uncertainty.

A Holistic Approach to Evaluating Research - Ofir, Zenda; Schwandt, Thomas; Duggan, Colleen; McLean, Robert (IDRC, 2016)

Building Bridges to an Uncertain Future Lived Now: Lessons from the Use of Participatory Action Research and Theory of Change Towards A Realistic Community-Based Participatory Monitoring and Evaluation System - Avila, Enrique M.; Tolentino, Lutgarda L.; Binondo, Claudia B.; Perez, Maripaz L.; Apgar, J. Marina (International Journal of Agriculture System, 2016)
Building on experience from the CGIAR Research Program on Aquatic Agricultural Systems implemented by WorldFish in the Visayas and Mindanao regions of the Philippines, known as the VisMin Hub, we describe the development and evolution of a monitoring and evaluation (M&E) system emerging from the facilitated action-reflection cycles of testing and adopting theories of change carried out with community partners through participatory action research (PAR). The former guides our community partners and us, as members of the potentially emergent PAR groups, towards the realization of the community’s vision; the latter facilitates learning to understand what, how and why change is unfolding. Unlike the conventional M&E system where indicators are pre-set at the beginning of program implementation, these processes result in an organically-evolved, communitybased participatory M&E system that is continuously revised according to contexts to guide communities towards realizing their visions. Its ultimate outcome is enhanced people’s capacity to own the product and process, giving rise to an internally-driven change. Towards the end, the paper offers an iterative discussion of learnings from implementing such an approach.
Keywords: Aquatic agricultural systems; CGIAR; Community-based participatory MEL; Learning; Participatory action research; research in development; theory of change

Program Cycle Road Map - USAID (2016)

Forward Look - A vision for the World Bank Group in 2030 - World Bank (World Bank, 2016)

Experiential Learning: Fostering lasting behavioural change - Norton, Brittney M. (Mercy Corps, 2016)
The term ‘experiential learning’ is often mistakenly used to describe any learning experience that involves participatory activities. This paper presents an overview of what true experiential learning is and how this form of learning allows for real-world application - thus promoting lasting behavioural change. Furthermore, it explains how experiential learning was adopted as the methodological core of the Prospects psychosocial programme in Liberia, which builds ‘pre-employment skills’ in 3,500 vulnerable youth aged 15-24 years. The goal of the paper is to provide other youth and education development practitioners with a resource that can be used to strengthen youth and behaviour change programmes through the incorporation of the experiential learning theory. In addition, this paper explains its application in the Prospects programme, before concluding with key considerations of such a design. 1

Forget the money: De-linking technical assistance - Manuel, Clare (DFID-LASER Programme, 2016)

State Accountability and Voice Initiative (SAVI) - Approach Paper Series - SAVI (DFID, 2016)
We are piloting a new approach to identifying and supporting our partners. This breaks with convention in many ways in order to improve impact. Our approach is summarized in the Introduction to SAVI’s way of working. We have broken our approach down into key components – depicted in the form of our ‘knowledge tree’ –...
Keywords: IMPORTANT

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...

The Future is a Choice: The Oxfam Framework and Guidance for Resilient Development - Jeans, Helen; Thomas, Sebastien; Castillo, Gina (Policy & Practice, 2016)
This guide provides a framework for Oxfam staff to design programmes and campaigns that contribute to resilient development. Oxfam defines resilience as ‘the ability of women and men to realize their rights and improve their well-being despite shocks, stresses

Clearing the fog: new tools for improving the credibility of impact claims - Befani, Barbara; D'Errico, Stefano; Booker, Francesca; Giuliani, Alessandra (iied Briefing Papers, 2016)
Development actors facing pressure to provide more rigorous assessments of their impact on policy and practice need new methods to deliver them. There is now a broad consensus that the traditional counterfactual analysis leading to the assessment of the net effect of an intervention is incapable of capturing the complexity of factors at play in any particular policy change. We suggest that evaluations focus instead on establishing whether a clearly-defined process of change has taken place, and improve the validity and credibility of qualitative impact statements. IIED research in Uganda shows that the methods of process tracing and Bayesian updating facilitate a dialogue between theory and evidence that allows us to assess our degree of confidence in ‘contribution claims’ in a transparent and replicable way.

When and how to develop an impact-oriented monitoring and evaluation system - Peersman, Greet; Rogers, Patricia; Guijt, Irene; Hearn, Simon; Pasanen, Tiina; Buffardi, Anne (2016)
This guidance note focuses on: • what an impact-oriented monitoring and evaluation system entails • why an organisation may want to establish such a system • when integrating an impact-orientation into an monitoring and evaluation system is most useful • what should be considered in developing the monitoring and evaluation system, or in tweaking an existing system, to become more impact-focused. The primary audience for this guidance note is internal and external monitoring and evaluation advisors involved in designing and implementing, and/or assessing monitoring and evaluation systems to include a focus on impact. It will also be useful for senior management of organisations who need to know how best to plan for a sustainable monitoring and evaluation system that supports impact assessment or to adapt an existing system to incorporate an impact perspective.

Thinking and Working politically to support developmental leadership and coalitions: The Pacific Leadership Program - Denney, Lisa; McLaren, Rebecca (DLP Program, 2016)

Everyday Political Analysis - Hudson, David; Marquette, Heather; Waldock, Sam (Developmental Leadership Program, 2016)
This short note introduces a stripped-back political analysis framework designed to help frontline development practitioners make quick but politically-informed decisions. It aims to complement more in-depth political analysis by helping programming staff to develop the 'craft' of political thinking in a way that fits their everyday working practices. Everyday Political Analysis involves two steps: Understanding interests: What makes people tick? Understanding change: What space and capacity do people have to effect change? For each step five questions, accompanied by prompts, aim to help staff to conduct quick political analysis. The EPA framework can be used at any stage of the aid management cycle, and can help users to respond rapidly to unexpected change. We are keen to hear back from people on their experience of using EPA to help us adapt the framework. Was it useful (or not)? Do people tend to use just one or both steps? Are there missing statements or prompts that would improve the analysis? Please email us at info [at] dlprog.org.

Monday morning in Kigali: what do you do when you get off the plane? Practical guidance for PDIA practitioners - LASER (DFID-LASER Programme, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Monday morning in Kigali January 2016 - what do you do when you get off the plane? Practical guidance for PDIA practitioners
Keywords: IMPORTANT; Practice

DFID Smart Rules: Better Programme Delivery - version VI (2016.10) - DFID (DFID, 2016)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice

Is DFID Getting Real About Politics?A stocktake of how DFID has adopted a politically-informed approach (2010-2015) - Piron, Laure-Hélène; Baker, Aislin; Savage, Laura; Wiseman, Katie (DFID, 2016)
1. Background This internal stocktake assesses whether DFID is “getting real about politics” - how it is taking power and politics into account in all its operations. Country Poverty Reduction Diagnostics undertaken by DFID teams identify politics as the most frequent barrier to poverty reduction and growth. The UK 2015 Aid Strategy has committed DFID to spending 50% of Official Development Assistance (ODA) in fragile states. This requires a “patient, long-term approach” to addressing barriers to peace and stability which are fundamentally political, rather than purely financial or technical. The stocktake is based on three DFID offices case studies (Democratic Republic of the Congo, Pakistan and Malawi) as well as extensive internal and external consultations between June and December 2015. It provides illustrations of how DFID is evolving but does not systematically offer evidence of development impacts or non-country work, as this would have required a different methodology. 2. What does it mean to take politics into account? Politically-informed approaches are based on a large body of evidence that confirms the importance of institutions and politics for sustainable development. External assistance needs to support locally-led change. Success depends on timing, context, political processes and local actors. Desirable outcomes are hard to achieve and difficult to predict. Politically-informed approaches improve development effectiveness through:  The ‘what’: political goals, using development assistance to shift how power is distributed in the economy and society. The two main elements are: aiming for long term transformation of institutions; and supporting locally-led change processes more likely to be sustainable and successful: locallyowned (i.e. with local salience) and locally-negotiated.  The ‘how’: politically-smart methods, with greater realism and feasibility. The three main elements are: understanding power and politics in a specific context in order to identify opportunities and barriers for change; influencing and stakeholder management skills; and proactive risk management. To influence DFID operations, a politically-informed approach needs to be iterative, not one-off. The explicit understanding of context, whether formal setpiece studies or more routine analysis, should inform policy and programme decisions, from high level strategic choices, to day-to-day implementation, for both international policy and country support. This is a dynamic process: as the context evolves and lessons are learned about what works, analyses and decisions are updated. These are the principles behind the ‘flexible and adaptive’ agenda.

SPACES MERL: Systems and Complexity White Paper - USAID (2016)
The Strategic Program for Analyzing Complexity and Evaluating Systems (SPACES MERL) project is an activity funded by USAID’s Global Development Lab and the Bureau for Policy, Planning and Learning (PPL). This three-year activity aims to bring a variety of tools and methodologies that decision-makers can use (alone or in combination) to provide comprehensive systems analysis. The activity is being implemented from 2015 to 2018 by a consortium of organizations expert in systems and complexity, including the Global Obesity Prevention Center (GOPC) at Johns Hopkins University (Prime), Global Knowledge Initiative (GKI), LINC and ResilientAfrica Network (RAN). This Systems and Complexity White Paper is a collaborative effort of the SPACES MERL team, designed to frame the international development landscape, with particular reference to USAID-funded activities, for application of systems and complexity approaches to design, monitoring and evaluation. Customized to the systems and complexity layperson with in-depth knowledge of international development practice, the objectives of this white paper are three-fold:  Provide an overview of systems and complexity practice, its current state of application and relevance to international development practice;  Establish a taxonomy of systems and complexity tools, highlighting the fit of those offered by SPACES MERL within the wider landscape; and  Review and provide information on application of SPACES MERL tools, their purpose and construction, required data, and their applicability to specific contexts.